2019
DOI: 10.1155/2019/8757685
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Verum and Sham Acupuncture in Fibromyalgia Syndrome: A Systematic Review and Meta-Analysis

Abstract: Objectives. Acupuncture is often used for relieving symptoms of fibromyalgia syndrome (FMS). Our aim is to ascertain whether verum acupuncture is more effective than sham acupuncture in FMS. Methods. We collected RCTs to investigate the effects of verum acupuncture and sham acupuncture on pain, sleep quality, fatigue, and general status in FMS patients. The databases used for data retrieval were PubMed, Central Cochrane, EMBASE, PsycINFO, CNKI, VIP, OASIS, KoreaMed, and RISS. Selection/exclusion from the retri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
1
15

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(60 citation statements)
references
References 56 publications
2
42
1
15
Order By: Relevance
“…The role of magnesium in FMS pathophysiology is still controversial, although it is reported that the magnesium deficiency can cause muscle cramps, weakness, fatigue, and asthenia [31]. Though there has been evidence that there is a low level of serum magnesium in FMS patients, a strong correlation with the severity of the FMS symptoms has not yet been demonstrated [8,[32][33][34][35]. However, magnesium citrate treatment resulted in a significant reduction in pain symptoms and in the FIQ-R score [15].…”
Section: Nutrient Considerationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The role of magnesium in FMS pathophysiology is still controversial, although it is reported that the magnesium deficiency can cause muscle cramps, weakness, fatigue, and asthenia [31]. Though there has been evidence that there is a low level of serum magnesium in FMS patients, a strong correlation with the severity of the FMS symptoms has not yet been demonstrated [8,[32][33][34][35]. However, magnesium citrate treatment resulted in a significant reduction in pain symptoms and in the FIQ-R score [15].…”
Section: Nutrient Considerationsmentioning
confidence: 99%
“…A recent systematic review and meta-analysis of randomized controlled trials reported that acupuncture therapy is an effective, safe, and recommended treatment for management of patients with FMS [53]. Other analyses have provided evidence that verum acupuncture was more effective than sham acupuncture for pain relief, improving sleep quality, and reforming general status in FMS post-treatment, although evidence that it reduces fatigue was not found [33]. There is also evidence that acupuncture potentiates the effect of antidepressants and exercise on pain by up to 30%, with poor, almost nil, adverse effects [17].…”
Section: Acupuncture Considerationsmentioning
confidence: 99%
“…First of all, this research can be criticized for the fact that no control group was conducted for sham acupuncture to distinguish the placebo components from the verum ones of the treatment. However, on the basis of what has already been observed by some researchers, the use of a sham acupuncture (both minimally invasive and in points outside the meridian), especially in the field of painful diseases, instead of reducing the bias probably introduces others since it is a sensory stimulation not inert [34,35].…”
Section: Discussionmentioning
confidence: 99%
“…Table 7 summarizes the articles identified after searching for each specific modality from a pool of 348 articles. There were a total of 21 articles: 5 CPGs, 14,17,29,32,33 4 RCTS, [34][35][36][37] and 12 SRs, [38][39][40][41][42][43][44][45][46][47][48][49] as shown by condition and therapy in Table 7.…”
Section: Literature Search and Evaluationmentioning
confidence: 99%
“…Spinal manipulation 97 Myofascial release 97 Acupuncture 44 LLL therapy 43,49 c. Combined active and passive: multidisciplinary rehabilitation d. Mind-body interventions, including CBT, mindfulness meditation, yoga, and t'ai chi, qigong…”
Section: Diagnostic Considerations For Fibromyalgiamentioning
confidence: 99%